PELAKSANAAN LAYANAN BIMBINGAN KEMANDIRIAN PADA EKS PSIKOTIK DI RUMAH PELAYANAN SOSIAL EKS PSIKOTIK HESTINING BUDI KLATEN - Hanif Sandya Eko Putro (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2019)
Ex Psychotics are people who have experienced mental disorders and are declared cured of mental hospitals, but they do not have proper independence. Therefore, they need an independent guidance service. This research is intended to find out the process of implementing independence guidance services, supporting and inhibiting factors and the form of independence in ex psychotics at the Social Services House of the former Psychotic Hestining Budi Klaten This study uses a descriptive qualitative approach. The subjects of this study were four social workers and three beneficiaries selected using a purposive sampling technique at the Social Services House of the Former Psychotic Hestining Budi Klaten. With data collection techniques in the form of interviews, observation, and documentation. In testing the validity of data using source triangulation. While for data analysis techniques using several stages starting from data collection (data collection), data reduction (data reduction), presenting data (data display), and drawing conclusions (conclusion: drawing / verifying). The results of this study that the implementation of independence guidance services at the Social Services House of Ex-Psychotic Hestining Budi Klaten is carried out through several stages including (1) Planning, namely social workers determine in advance the material to be given to ex psychotics; (2) Implementation, namely the provision of material to ex psychotics starting from Daily Living Activist (DLA) guidance, physical guidance, mental guidance, social guidance, and skills guidance; (3) Evaluation, namely giving an assessment from the results of the implementation of guidance; (4) Follow-up, which is the step to proceed to further guidance. Inhibiting factors in the implementation of independence guidance services such as facilities and infrastructure, Human Resources, ex-psychotic conditions, society, and difficulties in selling ex-psychotic works, while supporting factors start from the existence of good cooperation between social workers and outside parties/institutions, facilities and infrastructure, and family. The success of the independence guidance service process, namely ex psychotics is able to be independent in taking care of themselves, interact socially, carry out worship, and skills. Keyword: Independent guidence service, ex psikotik